Systematic Literature Review: Filsafat Paulo Freire dalam Dunia Pendidikan Berbasis Kritis dan Humanisasi : Systematic Literature Review: Paulo Freire's Philosophy in the World of Critical and Humanistic Education - Cahyani, Indah Galis; Wibowo, Sigit (Undiksha, 2025)
Traditional education systems are often authoritarian and dehumanizing, failing to encourage critical awareness and social transformation. This article examines the contribution of Paulo Freire's philosophy in addressing these issues through a critical and humanistic approach to education. This study uses a Systematic Literature Review method on 15 scientific articles published between 2014 and 2024. The findings indicate that Freire's principles, such as dialogue, conscientização (critical awareness), and a humanistic approach, can address dehumanization in conventional educational systems. This approach is proven relevant in the context of modern education, which demands justice, inclusivity, and empowerment. This article recommends the integration of Freire's values into formal and informal curricula to achieve sustainable transformative education.